Clinical and Immunological Features of Osteoarthritis: The Role of Adipocytokines and Pathogenetic Phenotyping (The Peerian Journal, 2025)
To evaluate the association between Metabolic Syndrome (MS), clinical characteristics, and immunological status in patients with Osteoarthritis (OA), and to determine the prognostic significance of adipocytokines and pro-inflammatory cytokines.